2018
DOI: 10.1186/s12889-018-5533-3
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of cesarean section births in private sector health facilities- analysis of district level household survey-4 (DLHS-4) of India

Abstract: BackgroundWorldwide rising cesarean section (CS) births is an issue of concern. In India, with increase in institutional deliveries there has also been an increase in cesarean section births. Aim of the study is to quantify the prevalence of cesarean section births in public and private health facility, and also to determine the factors associated with cesarean section births.MethodsWe analyzed data from district level household survey data 4 (DLHS-4) combined individual level dataset for 19 states/UTs of Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

34
92
7
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(135 citation statements)
references
References 34 publications
34
92
7
2
Order By: Relevance
“…This present study found that 18.5% of women who delivered in health facilities 5 years preceding the survey delivered their babies through CS, a figure that exceeds the threshold of 5-15% recommended by WHO [7]. This corroborates the findings in previous studies in low-and -middle income countries such as Pakistan [1], Egypt, [11], Bangladesh [12], Ethiopia [31], India [32], Jordan [33] and Tanzania [34]. An improved propensity toward available medical interventions and continued discouragement of VD after previous CS may have added to the recent increase in CS rates as noted in other countries [35].…”
Section: Discussionsupporting
confidence: 91%
“…This present study found that 18.5% of women who delivered in health facilities 5 years preceding the survey delivered their babies through CS, a figure that exceeds the threshold of 5-15% recommended by WHO [7]. This corroborates the findings in previous studies in low-and -middle income countries such as Pakistan [1], Egypt, [11], Bangladesh [12], Ethiopia [31], India [32], Jordan [33] and Tanzania [34]. An improved propensity toward available medical interventions and continued discouragement of VD after previous CS may have added to the recent increase in CS rates as noted in other countries [35].…”
Section: Discussionsupporting
confidence: 91%
“…This is true irrespective of woman reporting any complication either during gestation or at the time of delivery. 5,26 The assessment of qualitative information also supplemented these quantitative inferences.…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that higher socio-economic status provides sufficient finances to bear the higher expenditure of caesarean surgery. Thus, caesarean section is more prevalent in women belonging to higher socio-economic class [32]. On the other hand, women belonging to lower socioeconomic status might not be able to afford the expenses of caesarean delivery or they do not have access to the obstetric care facilities required for caesarean delivery.…”
Section: Discussionmentioning
confidence: 99%